2019
DOI: 10.1016/j.enggeo.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

National geohazards mapping in Europe: Interferometric analysis of the Netherlands

Abstract: The launch of Copernicus, the largest Earth Observation program to date, is significant due to the regular, reliable and freely accessible data to support space-based geodetic monitoring of physical phenomena that can result in natural hazards. In this study, wide area interferometric synthetic aperture radar (InSAR) capability is demonstrated by processing 435 Copernicus Sentinel-1 C-Band SAR images (May 2015 -May 2017) using the Intermittent Small Baseline Subset (ISBAS) method to produce a wide-area-map (WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…The Subsidence/Uplift class (4.4%) includes surface deformation analyses performed at a large, regional or national scale, in which both subsidence and uplift phenomena can be identified. Case studies were identified in Netherlands, such as surface deformation analyses performed over the whole national territory [176][177][178][179] or monitoring works of the water defence structure of Waddenzee and IJsselmeer [180,181]. Two other scientific contributions focused on the Polish and Lithuanian Baltic coastal areas [105] and the surface displacement pattern affecting the permafrost areas in northern Norway [75].…”
Section: Field Of Applicationmentioning
confidence: 99%
“…The Subsidence/Uplift class (4.4%) includes surface deformation analyses performed at a large, regional or national scale, in which both subsidence and uplift phenomena can be identified. Case studies were identified in Netherlands, such as surface deformation analyses performed over the whole national territory [176][177][178][179] or monitoring works of the water defence structure of Waddenzee and IJsselmeer [180,181]. Two other scientific contributions focused on the Polish and Lithuanian Baltic coastal areas [105] and the surface displacement pattern affecting the permafrost areas in northern Norway [75].…”
Section: Field Of Applicationmentioning
confidence: 99%
“…The new generation of SAR sensors (e.g. Sentinel-1, ALOS2 PALSAR2, TerraSAR-X, COSMO-Skymed and Radarsat-2) are now regularly operate in orbit with very short revisit time which enable InSAR achieve wide-area monitoring of ground displacement at high precision (Gee et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the new generation of SAR sensors including Sentinel-1, ALOS2 PALSAR2, TerraSAR-X, COSMO-Skymed which operate in orbit with short revisit cycles enable the widearea monitoring of ground displacement at high precisions nowadays (Gee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%